TNAP as a therapeutic target for cardiovascular calcification: a discussion of its pleiotropic functions in the body. Issue 1 (18th October 2020) - Goettsch, Claudia; Strzelecka-Kiliszek, Agnieszka; Bessueille, Laurence; Quillard, Thibaut; Mechtouff, Laura; Pikula, Slawomir; Canet-Soulas, Emmanuelle; Luis, Millan Jose; Fonta, Caroline; Magne, David
Abstract: Cardiovascular calcification (CVC) is associated with increased morbidity and mortality. It develops in several diseases and locations, such as in the tunica intima in atherosclerosis plaques, in the tunica media in type 2 diabetes and chronic kidney disease, and in aortic valves. In spite of the wide occurrence of CVC and its detrimental effects on cardiovascular diseases (CVD), no treatment is yet available. Most of CVC involve mechanisms similar to those occurring during endochondral and/or intramembranous ossification. Logically, since tissue-nonspecific alkaline phosphatase (TNAP) is the key-enzyme responsible for skeletal/dental mineralization, it is a promising target to limit CVC. Tools have recently been developed to inhibit its activity and preclinical studies conducted in animal models of vascular calcification already provided promising results. Nevertheless, as its name indicates, TNAP is ubiquitous and recent data indicate that it dephosphorylates different substrates in vivo to participate in other important physiological functions besides mineralization. For instance, TNAP is involved in the metabolism of pyridoxal phosphate and the production of neurotransmitters. TNAP has also been described as an anti-inflammatory enzyme able to dephosphorylate adenosine nucleotides and lipopolysaccharide. A better understanding of the full spectrum of TNAP's functions is needed to better characterize the effects of TNAP inhibition in diseases associated with CVC. In this review, after a brief description of the different types of CVC, we describe the newly uncovered additional functions of TNAP and discuss the expected consequences of its systemic inhibition in vivo . Graphical Abstract: